Blood pressure measurements over thin and thick sleeves in the frail elderly. Issue 1 (February 2018) - Ozone, Sachiko; Sato, Mikiya; Takayashiki, Ayumi; Sato, Takuya; Matsushita, Aya; Yoshimoto, Hisashi; Maeno, Tetsuhiro
Abstract : Objective: Blood pressure (BP) measurement is recommended on bare arms, but undressing the arms for BP measurements is often difficult for frail elderly individuals. We aimed to assess the accuracy of BP measurements over arms with thin and thick clothing among the frail elderly. Participants and methods: This is a cross-sectional study. Individuals aged 65 years or older were recruited from three long-term care facilities in Japan between April and May 2016. The main outcome measures were BP measurements (a) on a bare arm, (b) over a thin shirt, (c) over a thin shirt and a cardigan, and (d) over the sleeve of a thin shirt and a cardigan rolled up to the elbow. BP was compared across measurements using the paired t -test and multiple analysis of variance adjusting for sex and treatments for hypertension. Results: Of 147 participants, 23.8% were men. The mean age of the participants was 87.2 years (SD: 7.8). The mean (SD) BP on a bare arm, over a shirt, over a shirt and a cardigan, and over a rolled-up sleeve were 128.8 (20.0)/69.3 (13.2), 131.0 (22.2)/73.9 (15.2), 136.9 (22.2)/78.9 (15.8), and 136.4 (26.0)/80.7 (15.9) mmHg, respectively. BP measurements over clothed arms were significantly higher than bare arm measurements. BP differences were significant when measured over a cardigan after adjusting for sex and treatments for hypertension. Conclusion: In the elderly, clothing has a significant effect on BP measurements. The arms should be undressed as much as possible for BP measurements in the elderly.